Do almonds (Prunus amygdalus Mill.) alpha-amylase germinating seedlings have a beta/alpha fold? - Hermi S.; Bahri S. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Alpha-amylases have been well characterized in microorganisms and mammals. Very little is known about plant amylases. A previous study has allowed us to demonstrate the presence of alpha-amylase in germinated almond seedling (Prunus amygdalus Mill.) var ‘Tuono Mazzetto’ (Rosaceae family). The enzyme activity was optimal at the 4th day of germination with a Vmax = 2.5 UI and Km = 6.32 mM. In the current study, our aim was to propose in silico, by comparative modelling, a putative homologous model of three-dimensional (3D) structure of Prunus persica alpha-amylase, a species from the same family. The Prunus persica alpha-amylase structure shows a beta/alpha fold with small deviation from the template 3D coordinates even in the loop regions. The geometry of the catalytic site is preserved. The Ramachandran plot confirmed that the proposed model might be of a good quality. Alpha-amylase structure from Prunus Persica was also compared to a porcine (Sus scrofa) one, indicating the structural homology of these two different species. Combination of bioinformatics and biochemistry would allow us to better understand almond alpha amylase function.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)